Strengthening the Connection between Differentiated Instruction Strategies and Teaching Personal and Social Responsibility: Challenges, Strategies, and Future Pathways. Issue 5 (12th June 2020) - Melo, Marta; Santos, Fernando; Wright, Paul M.; Sá, César; Saraiva, Linda
Abstract : The Teaching Personal and Social Responsibility (TPSR) model has been considered a valuable tool to help students strive to reach their potential in physical education, sport and life. One of the core pedagogical beliefs behind TPSR is that learning experiences should be tailored to recognize and meet students' developmental needs and the abilities of each learner. The purpose of this article is to provide insight on the challenges, strategies, and future pathways associated with strengthening the connection between differentiated instruction strategies and TPSR.